Is there a role for traction forces exerted at the polar regions in the cytokinesis of adherent cells? - Foo, Jasmine Mao Shan. (2009)
In cytokinesis, the division of the cytoplasm of the mother cell to form two daughter cells has long been known to be accomplished by furrow ingression through constriction of the contractile ring. Recent studies suggested that adherent cells could divide without the contractile ring, in an adhesion-dependent manner by producing traction forces. The aim of this study was to investigate the role of polar traction forces during cytokinesis of adherent cells. Normal rat kidney epithelial cells were cultured on polyacrylamide substrates of different stiffness to observe if the traction force affects the furrow ingression during cytokinesis. I found that cells that adhered firmly to substrates could produce opposite traction forces at polar regions during cell division, leading to a slight delay in cytokinesis. My results suggest that polar traction forces negatively regulate dividing cells’ separation into daughter cells by pulling them apart during cytokinesis.